Serum interleukin 12 concentration in juvenile chronic arthritis. Issue 7 (1st July 1998) - Gattorno, M; Picco, P; Vignola, S; Stalla, F; Buoncompagni, A; Pistoia, V
Abstract : OBJECTIVES: The aim of this study was to evaluate serum interleukin (IL) 12 concentration in patients with juvenile chronic arthritis (JCA), according to disease subtype, activity, and duration. IL12 has been demonstrated to prime the selective expansion of T helper (Th) cells with a Th1-type pattern of cytokine production. METHODS: Sixty eight serum samples from 50 JCA patients (12 systemic, 12 polyarticular, 26 pauciarticular), 20 serum samples from age matched healthy controls were tested with two different immunoassays specific for total IL12 (p40 and p70 heterodimer) and for IL12 (p70) heterodimer, respectively. The following disease activity parameters were evaluated: (a) presence of arthritis at least in one joint, (b) physician global estimate of disease activity, (c) disability index according to the Childhood Health Assessment Questionnaire (CHAQ), (d) C reactive protein (CRP). RESULTS: Total IL12 (p40 and p70 heterodimer) was significantly higher in JCA active patients than in those on clinical remission and in healthy controls (p < 0.001). Conversely, detectable concentrations of IL12 (p70) heterodimer were found in three active JCA patients only. Moreover, total IL12 (p40 and p70 heterodimer) showed a significant negative correlation both with time from disease diagnosis ( r = −0.29, p = 0.04) and, for the pauciarticular subgroup, with disease activity duration ( r = − 0.71, p < 0.001). CONCLUSIONS: This study shows that the p40 moiety of IL12 is increased in serum samples from active JCA patients, especially in the earliest phases of the disease, whereas biological active IL12 (p70) heterodimer is virtually undetectable.